The significant role of Shariah Advisory Council (SAC) in dispute resolution mechanisms: the evolution of regulatory framework in Malaysia - Mohd. Zain, Nor Razinah; Hasan, Aznan (MARIS, 2022)
The continuous growth of Islamic financial services globally indicates the growing interest and acceptance from the relevant stakeholders for ethical financing and faith-based financial system. A progressive demonstration in product innovations and governance can be traced in many countries that participate in the Islamic financial services industry (IFSI). However, such demonstration is still lacking when it comes to dispute resolution mechanisms. Depending on regulatory challenges that need to be faced by the IFSI in these respective countries, there is a crucial need to find a suitable dispute resolution forum that is able to appreciate both of the existing laws and the Shariah-compliance nature that may be questioned when a dispute arises. Looking close to the evolution of IFSI in Malaysia, they provide an innovative way in their regulatory system to impose a serious consistency in adhering to Shariah-compliance nature and the existing laws in their industry. With the increasing number of legal disputes that emerged from IFSI, the introduction of Shariah Advisory Council (SAC) gains a significant role in crafting the way for a better dispute resolution strategy. By adopting qualitative and doctrinal legal methodologies, this research is conducted to trace the crucial role of SAC in dispute resolution mechanisms within Malaysian regulatory framework. It is found that the involvement of SAC in the process of legal settlement is a unique legal innovation that may be followed in other jurisdictions.